The change makers : 25 leaders in their own words - Carney, Shaun, 1957- (Melbourne University Press, 2019)
Good leadership. Why is it so elusive? Are there successful traits that can be transferred from one field to another, or is it a constant application of imagination to the changing challenges? How do you take others with you? Now more than ever we need leaders who can be strong yet humble, bold and assertive when it counts but have the capacity to listen and learn, who can motivate and influence, and who can get the best out of those around them. Twenty-five outstanding Australian leaders-from diverse worlds such as science, the police force, a netball team, a spy agency, emergency medicine, business, politics and unionism-share their insights and lessons on the essence of inspiring leadership.